Religious Attributions and Proximity of Influence: An Investigation of Direct Interventions and Distal Explanations. - Weeks, Matthew; Lupfer, Michael B. (Journal for the Scientific Study of Religion (Wiley-Blackwell), 2000)
Investigations into religious attributions have focused on attributer's immediate, proximal causes of events, paying little attention to underlying, distal explanations. In an effort to explain the relatively low incidence of religious attributions and further a new model of proximal-distal attributions, we present two experiments investigating the proximal and distal use of religious and nonreligious supernatural attributions. Participants in both studies were presented a series of sixteen vignettes that varied on several attribution-relevant dimensions. After reading each vignette, subjects gave an initial explanation for the event, and were then probed for any underlying explanations. Experiment 1 used an interview format that allowed participants maximum latitude when explaining the event's outcome. Consistent with our predictions, participants perceived God as having a greater distal than proximal influence, though this difference was not evident for attributions to Satan or nonreligious supernatural agents. Experiment 2 was performed via a microcomputer, with a participant's initial attributional response branching to a set of appropriate distal explanations. Overall, the results suggest that attributer's perceive God working through indirect influences rather than direct intervention, with this effect being moderated by the attributer's level of religiosity. This pattern was evident in the use of God as a distal explanation as well as in the distal explanations to proximal attributions to God.